Lidocaine Versus Ketamine Pretreatment on Propofol Injection Pain - Murad Khudadad Boujan, Amir; fazeel Kareem, Nashmeel; A. Marouf, Amanj; Abdullah Ahmed Fahmi, Saman; Qadir Mahmood, Salah (Kurdistan Journal of Applied Research, 2019)
Propofol is commonly used intravenous anesthesia induction drug but it causes ache upon use, many methods with different results, have been suggested to prevent this pain, the current research was concluded in order to investigate the impact of lidocaine, ketamine in reducing the ache on giving intravenous propofol. This study is randomized controlled clinical trial lasting from June 2015 to November 2015 during which 107 consenting (ASA1 and ASA2) patients were prepared for elective operation with general anesthesia. They randomly split to three subgroups, A cannula (size20) used in the dorsum hand veins, standard monitor was established patients received either 2mL (40 mg) of lidocaine or 2mL (20mg) of ketamine and 2 mL of saline 1 min before injection 2.5 milligram per kilogram propofol. ache severity observed by using four number pain scale, zero = none, one= mild pain, two = moderate pain, and three = intense pain. Atracurium used for indotracheal intubation, isoflurane and fentanyl for anesthesia maintenance. There were no variations between the study groups regarding ASA status, Sex, age. The incidence of ache when injecting propofol were observed in the normal saline group was 86.5% and it was more than ketamine group 0% and lidocaine group 20% (p=0.0002). In the normal saline pretreatment group 8.1% of the patient experienced severe pain, compared with 0% in the lidocaine and ketamine. It can be concluded that intravenous ketamine and lidocaine were equally effective in preventing Ache during propofol injection.